Metastatic cutaneous Crohn’s disease as an important differential diagnosis of granulomatous skin disease - Murilo C. Peretti (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2016)
Patients with Crohn’s disease may show extraintestinal manifestations, including cutaneous, whose frequency ranges from 2% to 34%. Metastatic cutaneous Crohn’s disease is considered a specific and rare manifestation, since the histopathology reveals granulomatous pattern with the same characteristics of the underlying bowel condition. The objective of this study is to report two cases of metastatic cutaneous Crohn’s disease confirmed by histopathologic analysis, after excluding other granulomatous skin diseases. Case 1: Adult woman with pruritic erythematous scaly plaques disseminated on the upper limbs. Case 2: Adult man with grayish hyperchromic plaque infiltrated on the left buttock.